Community pharmacists’ history taking practice in responding to acute uncomplicated cystitis: A simulated patient study from Sudan - Riham M. Hamadouk; Esra D. Albashair; Einass M. Alshareif; Ali Awadallah Saeed; Bashir A. Yousef (PLoS ONE, 2026)
Background Today, community pharmacists’ responsibilities have expanded beyond the traditional role to include the management of minor ailments. Acute uncomplicated cystitis is one of the most prevalent medical conditions seen in primary healthcare and can be managed by community pharmacists (CPs). Objectives To evaluate community pharmacists’ history-taking practice when responding to patients with acute uncomplicated cystitis. Methods A cross-sectional simulated patient study was conducted from November 2022 to January 2023 in Khartoum locality targeting only pharmacists. Six trained female students played the simulation in which they pretended to have the clinical symptoms of acute uncomplicated cystitis and requested treatment for their condition. The Interactions during the simulation were documented immediately in a data collection form after each visit. Descriptive statistics were used to report the study outcomes. Results A total of 238 community pharmacies were visited. The majority of the pharmacists were female. The mean of the number of questions that were asked by the pharmacists was 1 (SD = 1.6) questions. Among the studied pharmacists, 45.4% asked at least one question during patient assessment. The most asked question was if the patient has a fever, representing 61 (25.6%) CPs, followed by if there is vaginal discharge, representing 38 (16%) CPs. In response to scenario 47 (19.7%) CPs decided to refer the patient to a physician, and 45 (18.9%) of the CPs advised the patient to increase water intake. Conclusions The study has revealed a poor history-taking practice towards acute uncomplicated cystitis during patient assessment. Further studies exploring pharmacists’ involvement in patient assessment are required. Strategies to improve community pharmacists’ practice, like continuing pharmacy education and providing a national guideline regarding patient assessment should be considered seriously.